The impact of social media-based support groups on smoking relapse prevention in Saudi Arabia. (June 2018) - Onezi, Hamidi Al; Khalifa, Mohamed; El-Metwally, Ashraf; Househ, Mowafa
Highlights: Tobacco smoking remains the leading cause of preventable death across the globe. The support provided by social media is more effective in smoking cessation after abstinence than traditional social support approaches. Individuals struggling to quit smoking should be encouraged to join the social media support groups of their interest so as to increase their cessation achievements. Abstract: Background and objective: Tobacco smoking remains a major preventable cause of mortality and morbidity across the globe. People who attempt to quit smoking often experience episodes of relapse before finally quitting. Understanding the part that social networking sites and social media can play in smoking cessation and prevention of relapse is important to aid the development of novel techniques to curb the smoking epidemic. This study investigated the use of extra-treatment provided outside of the formal healthcare setting, bolstered by online social support in order to prevent smoking relapse in Saudi Arabia. Methods: This cross-sectional study included 473 smokers taking part in smoking cessation intervention programs run by the Riyadh branch of King Abdul-Aziz Medical City and PURITY, a Saudi anti-smoking association. Only subjects who expressed an interest in quitting smoking, and those attempting to quit, were considered for inclusion. The sample was divided into three groups: subjects who subscribed to support groups on Twitter (n = 150), and WhatsApp (n = 150), and a control group of subjects who had not subscribed to any social media support groups (n = 173). Results: A significant difference was found between the mean average numbers of people who quit smoking among the three groups, with social media support proving to be more effective than other traditional methods. Our findings imply that Twitter and WhatsApp users found it easier to quit smoking than those who did not take part in these social media groups. Conclusion: Social media provides a good platform to discuss smoking cessation treatment, and thus reduce smoking relapses. Our findings support the suggestion that more social media support groups should be developed to help people to effectively cease smoking after abstinence. Individuals who struggle to quit smoking should be encouraged to join support groups on their social media platform of choice to increase their likelihood of quitting. Future studies should assess the effectiveness of social media to help people quit smoking by including a greater diversity of social media platforms, including Facebook, Snapchat, and Instagram.